2013
DOI: 10.1007/s11948-013-9498-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethicist as Designer: A Pragmatic Approach to Ethics in the Lab

Abstract: Contemporary literature investigating the significant impact of technology on our lives leads many to conclude that ethics must be a part of the discussion at an earlier stage in the design process i.e., before a commercial product is developed and introduced. The problem, however, is the question regarding how ethics can be incorporated into an earlier stage of technological development and it is this question that we argue has not yet been answered adequately. There is no consensus amongst scholars as to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Prior literature on VSD has focused on methodology (Cummings, 2006;Friedman & Kahn Jr., 2002;Friedman, Kahn Jr., Borning, & Huldtgren, 2013;Van den Hoven, Lokhorst, & Van de Poel, 2012;van den Hoven & Weckert, 2008), applications to current technological innovations (Aad Correlje, Eefje Cuppen, Marloes Dignum, 2015;Briggs & Thomas, 2015;van den Hoven, 2007) as well as to novel technologies (Dechesne, Warnier, & van den Hoven, 2013;Friedman, 1997;Friedman & Kahn Jr., 2000;Timmermans et al, 2011;van den Hoven, 2014;van Wynsberghe, 2013;Van Wynsberghe, 2016). Although these studies provide useful information, they do not take into account the reliability of all of the constituent parts of the VSD approach, in this case, the importance of moral intuition in conceptual investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature on VSD has focused on methodology (Cummings, 2006;Friedman & Kahn Jr., 2002;Friedman, Kahn Jr., Borning, & Huldtgren, 2013;Van den Hoven, Lokhorst, & Van de Poel, 2012;van den Hoven & Weckert, 2008), applications to current technological innovations (Aad Correlje, Eefje Cuppen, Marloes Dignum, 2015;Briggs & Thomas, 2015;van den Hoven, 2007) as well as to novel technologies (Dechesne, Warnier, & van den Hoven, 2013;Friedman, 1997;Friedman & Kahn Jr., 2000;Timmermans et al, 2011;van den Hoven, 2014;van Wynsberghe, 2013;Van Wynsberghe, 2016). Although these studies provide useful information, they do not take into account the reliability of all of the constituent parts of the VSD approach, in this case, the importance of moral intuition in conceptual investigations.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches often focus on how to identify bias or define guiding values at the outset, although bias and values can also arise as local phenomena that are "discovered" throughout design and development [25]. The second approach suggests that social scientists must be incorporated into the research process, which may produce more disagreement but arguably more discussion and deeper reflection on where ethics happens and where there are perceived to be "ethics free zones" that require attention [51]. Both approaches suit certain design settings better than others, with some studies noting "disjunctions" between AI and big data research methods and existing research ethics paradigms [31].…”
Section: Ethical Designmentioning
confidence: 99%
“…This proposal follows a complementary approach to continuous ethical reflection in research, by incorporating the general public or "community" into ethics analysis during the entire research cycle from research design to data collection, analysis, implementation and reflection on impact. According to [51], ethics must be part of the whole technological design process from the very beginning. A community participation approach to ethics empowers the general public with the tools to participate in discussions and debates about AI/NLP advances and their uses throughout the research lifecycle.…”
Section: Ethical Designmentioning
confidence: 99%
“…• It is directly related to the kind and amount of information that can be collected, to name a few (van Wynsberghe et al, 2013;van Wynsberghe and Robbins, 2013).…”
Section: The Context Of the Swarm And The Meaning Of Privacymentioning
confidence: 99%
“…The value is then a consequence of using the technology. With this in mind it is suggested that technologies can and should be made to intentionally realize desirable values while minimizing undesirable consequences ( van Wynsberghe and Robbins, 2013). This conclusion assumes a prospective approach to technology design and in this instance we are engaging in a retrospective ethical appraisal.…”
mentioning
confidence: 99%